Reflections about the book "Diritto come struttura e come forma” (Società e diritti, 2016)
The paper considers some significant aspects of the work of Alessandro Catelani entitled “Ildiritto come struttura e come forma”. The present work is the updated edition published in theyear 2013 of a previous work. The present work is related to the general theory of law, such as:the relationships between positive law and society; the formal and structural profiles of thelaw; the relations between law and justice; the protection of fundamental human rights. Somecriticisms are formulated about some classical conceptions of the law and of the legal system.The Author’s perspective is turned towards the doctrine of natural law or updated natural law.The work is the result of a great value commitment and originality of the Author’s thought.Key words: Legal-positivism, natural law, human rights